A Widely and Continuously Tunable Single-Mode Transmitter Based on a Hybrid Microcavity Laser - Miao-Qing Wang; Bin Zhang; Zhen-Ning Zhang; You-Zeng Hao; Zun-Hao Hu; Yue-De Yang; Jin-Long Xiao; António L. Teixeira; Yong-Zhen Huang (Photonics)
A method for achieving the single-mode and efficient unidirectional emission of a whispering gallery mode (WGM) semiconductor laser is presented herein. Hybrid square-rectangular lasers (HSRLs) and hybrid square/rhombus-rectangular lasers (HSRRLs) consisting of a Fabry–Pérot (FP) cavity and a square or rhombus cavity microcavity are described. In addition, a transmitter optical subassembly (TOSA) based on an HSRRL chip was fabricated, which has a wide and continuous wavelength tuning range. Wavelength channels from 1555.75 nm to 1568.15 nm with a spacing of 50 GHz were demonstrated with a good side mode suppression ratio (SMSR) and good output power. These devices have the potential to meet the typical requirements of optical communication networks.